1979
DOI: 10.1002/ajh.2830060110
|View full text |Cite
|
Sign up to set email alerts
|

Posttransfusion purpura: Therapeutic failure of PlAl‐negative platelet transfusion

Abstract: The effect of platelet type-specific transfusion in posttranfusion purpura is reported. Seven days after receiving 4 units of whole blood during total hip replacement a 69-year-old woman developed fulminant thrombocytopenic purpura. Her undiluted serum inhibited the clot retraction of PlAl-positive but not PlAl-negative blood. Anti-PlAl titer of her serum, determined by 51Cr platelet lysis technique, was 1:64. The serum had no lytic activity against platelet-rich plasma from two PlAl-negative donors. No anti-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…In support of this hypothesis, material containing platelet membrane glycoproteins lib/ Ilia, known to carry the Zw and Bak antigens can be detected in normal human plasma and serum [28,29]: simi lar observations have been made by two other groups [27,30]. It has also been shown that during the acute phase of the illness, transfused Zwa-negative donor platelets are rap idly destroyed [31]. However, further experimental investi gations have to be done to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…In support of this hypothesis, material containing platelet membrane glycoproteins lib/ Ilia, known to carry the Zw and Bak antigens can be detected in normal human plasma and serum [28,29]: simi lar observations have been made by two other groups [27,30]. It has also been shown that during the acute phase of the illness, transfused Zwa-negative donor platelets are rap idly destroyed [31]. However, further experimental investi gations have to be done to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…However, since most cases are due to anti-Zwa and the Zwa antigen frequency is 97.5% in the Caucasoid population, one must assume that most ran dom platelet transfusions are incompatible. Lack of effi cacy has also been reported for Zwa-negative platelets in isolated cases [19], A similar situation was observed in patient Gn. The patient did not at all respond to platelet transfusions, neither to random nor to sibling prepara tions.…”
Section: Aod (Moab Gi 5)supporting
confidence: 47%
“…Once this has developed after a transfusion, it is question able if transfusions with PlAl-negative blood are useful, since the PlAl-negative donor platelets may also be destroyed. Gerstner et al [6] found that their patient continued to bleed, with fatal result, when they tried to treat PTTP by transfusion of PlAl-negative platelets, but the number of transfused pla telets may have been too small: it is well known that platelets from at least 4-6 units of blood are necessary to achieve a clinical effect in ordinary cases of acute hemorrhag ic thrombocytopenia. It may be helpful in the future to store frozen PlAl-negative pla telets from several donors to treat severe cases of PTTP.…”
Section: Assay For Anti-plal Antibodies By the Pirc Testmentioning
confidence: 99%